PENINGKATKAN MOTIVASI BELAJAR MATA KULIAH SEJARAH PERADABAN ISLAM MELALUI METODE PEMBELAJARAN MIND MAPPING PADA PRODI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) STAI DARUSSALAM LAMPUNG - Damanhuri; Sumaryati (AZZAHRA, 2020)
A saturated attitude in learning is one of the problems that results in a decrease in student motivation in learning the History of Islamic Education, a solution must be sought. The mind mapping method applied in the course of the History of Islamic Civilization can be an alternative solution to overcome it. The aim of this research is to obtain an overview of the implementation of learning using the mind mapping method in increasing the motivation of the third semester students of the 2020/2021 Academic year of the PIAUD Study Program at STAI Darussalam in the History of Islamic Civilization course. The data were taken from PIAUD Semester III students, with classroom action research (PTK). To obtain complete data, this study uses a qualitative approach to retrieve, analyze, and process data and information that will be made to answer the problem being studied. The results showed that, the method of implementing mind mapping learning in the History of Islamic Civilization course could: (1) increase student motivation, (2) increase student activity and make quality, and (3) increase student learning to make creative and varied.